Feasibility, usability and acceptability of paediatric lung ultrasound among healthcare providers and caregivers for the diagnosis of childhood pneumonia in resource-constrained settings: a qualitative study. Issue 3 (11th March 2021) - Riaz, Atif; Cambaco, Olga; Ellington, Laura Elizabeth; Lenahan, Jennifer L; Munguambe, Khatia; Mehmood, Usma; Lamorte, Alessandro; Qaisar, Sana; Baloch, Benazir; Kanth, Neel; Nisar, Muhammad Imran; Volpicelli, Giovanni; et al.
Abstract : Objectives: Paediatric pneumonia burden and mortality are highest in low-income and middle-income countries (LMIC). Paediatric lung ultrasound (LUS) has emerged as a promising diagnostic tool for pneumonia in LMIC. Despite a growing evidence base for LUS use in paediatric pneumonia diagnosis, little is known about its potential for successful implementation in LMIC. Our objectives were to evaluate the feasibility, usability and acceptability of LUS in the diagnosis of paediatric pneumonia. Design: Prospective qualitative study using semistructured interviews Setting: Two referral hospitals in Mozambique and Pakistan Participants: A total of 21 healthcare providers (HCPs) and 20 caregivers were enrolled. Results: HCPs highlighted themes of limited resource availability for the feasibility of LUS implementation, including perceived high cost of equipment, maintenance demands, time constraints and limited trained staff. HCPs emphasised the importance of policymaker support and caregiver acceptance for long-term success. HCP perspectives of usability highlighted ease of use and integration into existing workflow. HCPs and caregivers had positive attitudes towards LUS with few exceptions. Both HCPs and caregivers emphasised the potential for rapid, improved diagnosis of paediatric respiratory conditions using LUS. Conclusions: This was the first study to evaluate HCP and caregiver perspectives of paediatric LUS through qualitative analysis. Critical components impacting feasibility, usability and acceptability of LUS for paediatric pneumonia diagnosis in LMIC were identified for initial deployment. Future research should explore LUS sustainability, with a particular focus on quality control, device maintenance and functionality and adoption of the new technology within the health system. This study highlights the need to engage both users and recipients of new technology early in order to adapt future interventions to the local context for successful implementation. Trial registration number: NCT03187067 .